MEKANISME RESTRUKTURISASI PEMBIAYAAN BERMASALAH KREDIT PEMILIKAN RUMAH DI MASA PANDEMI COVID-19 PADA BANK BTN SYARIAH KCS PASAR MINGGU - Satrio Adiputro (2023)
The restructuring is currently extended until 2023 because micro, small and medium enterprises are still affected by Covid-19. This study aims to find out and analyze the application of Bank BTN Syariah KCS Pasar Minggu to restructure problematic financing in mortgage products based on POJK number 11 / POJK.03 / 2020, POJK POJK POJK Number 48/POJK.03/2020 and Fatwa DSN MUI No. 48/DSN-MUI/II/2005. This research uses descriptive qualitative research methods. with the subjects taken are Unit Head Collection, 2 Staff Collection and 5 Mortgage Financing Restructuring Customers. This study uses primary and secondary data sources with interview, observation, and documentation data collection techniques. The results of this study show that the restructuring policy made by the OJK helps improve the economy in Indonesia with customers who can extend the payment time from the bank so that they can fulfill their payment obligations at a predetermined time.